Analisis Pencabutan Keterangan Terdakwa Dalam Berita Acara Pemeriksaan (BAP) Penyidikan Di Persidangan Terhadap Putusan Hakim - Sarimonang B Sinaga; Syafruddin Kalo; Muhammad Hamdan; Marlina Marlina (USU LAW JOURNAL, 2019)
Abstract. The revocation information of the defendant in the news of the proceedings (BAP) investigation at the trial which is not accompanied by a fundamental and logical reason then the legal position of the description of the defendant in the BAP the investigation can be "evidence hints". Legal considerations the judge refused the defendant's description of revocation reason Rhio Hendra Heriawan Ginting, et al in the BAP investigation because of the reasons stated for the removal of the defendant in the trial is not accompanied by a fundamental reason and logical, so that description the defendants contained in the BAP investigation can serve as evidence of the defendant's fault, the instructions while the matter with defendant Sandro Lumban Tobing, et al, the judge accepted the reasons for the removal because the defendants description accompanied by fundamental and logical reasons so that it captions the defendant in a BAP investigation does not have value of proof in proving fault of the defendant   Keywords : Revocation Information of The Defendant, The News of The Proceedings (NoP) Investigation, Consideration The Ruling of The Judges.